2000
DOI: 10.1034/j.1399-3003.2000.15d09.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of CPAP on daytime functioning in patients with sleep apnoea syndrome

Abstract: Daytime sleepiness, impaired cognitive performance and dysphoric mood are often present in patients with obstructive sleep apnoea syndrome (SAS). This prospective controlled study evaluates the effects of treatment with continuous positive airway pressure (CPAP) during 1 yr on daytime functioning in a large group of patients with SAS.The authors studied 80 patients (mean SEM 49 1 yrs) with SAS with a mean apnoea-hypopnoea index of 60 2 h -1 , and 80 healthy control subjects matched for sex and age (46 1 yrs.).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(94 citation statements)
references
References 29 publications
2
81
1
10
Order By: Relevance
“…[48][49][50][51] In addition, a recent case study has reported that suicidal ideation and depression were rapidly resolved in a patient with severe OSA after initiation of CPAP treatment. 52 Conversely, a number of studies have reported that CPAP does not affect depression scores in patients with OSA [53][54][55][56] ; however, a comprehensive meta-analysis has revealed that all of these negative studies investigated patients who had mild depression at baseline or excluded patients with major depressive disorder. 26 This study design may have skewed the study outcomes toward a negative result, as it has been reported previously that patients with OSA and more severe mood disorders receive the greatest benefit from CPAP.…”
Section: Confirmation Of Initial Diagnosismentioning
confidence: 99%
“…[48][49][50][51] In addition, a recent case study has reported that suicidal ideation and depression were rapidly resolved in a patient with severe OSA after initiation of CPAP treatment. 52 Conversely, a number of studies have reported that CPAP does not affect depression scores in patients with OSA [53][54][55][56] ; however, a comprehensive meta-analysis has revealed that all of these negative studies investigated patients who had mild depression at baseline or excluded patients with major depressive disorder. 26 This study design may have skewed the study outcomes toward a negative result, as it has been reported previously that patients with OSA and more severe mood disorders receive the greatest benefit from CPAP.…”
Section: Confirmation Of Initial Diagnosismentioning
confidence: 99%
“…Another large, prospective, controlled study examining the long-term effects of CPAP did not find any significant change in alcohol and coffee intake during the course of the study. 23 However, other dietary habits and caloric intake were not assessed. In a previous cross-sectional analysis of these APPLES In such models, Y is the dependent variable, a is the intercept with the Y axis, b 1 is beta coefficient for X 1 (1 st independent variable), b 2 is the beta coefficient for X 2 (2 nd independent variable), b 3 is the beta coefficient for X 3 (3 rd independent variable), etc.…”
Section: Discussionmentioning
confidence: 99%
“…Borak et al 73 found no improvement in emotional status relevant to depression after three and 12 months of CPAP therapy in 20 patients with severe OSA. Similarly Munoz et al 59 found no improvement of BDI scores in 80 subjects with severe OSA after 12 months of CPAP. In these negative studies the CPAP adherence was not monitored.…”
Section: Treatment Effectsmentioning
confidence: 99%
“…Serotonin has been implicated in depression. 59 Serotonin also influences upper airway dilator motor neurons through the hypoglossal nucleus, which is further reduced in sleep states. 58 Abnormalities in central and peripheral neurotransmission of serotonin have been implicated as a potential factor in depression.…”
Section: The Relationship Between Osa and Depressionmentioning
confidence: 99%
See 1 more Smart Citation